Practical Implementation of a Smart Home Model Using Arduino and Sensors - Soufiane Hachani; Okba Benelmir (ITEGAM-JETIA)
This paper focuses on the design and implementation of a physical model of a smart home with automated control systems to enhance resource management, energy efficiency, and user comfort. The model, built using wood and cardboard as primary materials, integrates multiple sensors connected to an Arduino microcontroller for autonomous operation. The smart home functions include: